Premenstrual syndrome among medical versus non-medical workers and its association with work-related quality of life - Nesma A. Mahmoud; Noha O. Frere; Nahla A. Zaitoun; Mai M. Zaitoun; Raghda A. Elshamy (SpringerOpen, 2024)
Abstract Background Premenstrual syndrome (PMS) is a commonly underestimated disorder that negatively impacts a woman's life. Medical workers, who live a more stressful life, may report an increased rate of PMS. Studies on the relationship between PMS and work-related quality of life for medical professionals are scarce, particularly in the Arab world. This study aimed to compare the frequency of PMS among medical versus non-medical workers at Zagazig University and to assess the association between PMS and their work-related quality of life. Methods A comparative cross-sectional study was conducted. The sample population consisted of 48 medical and 48 non-medical female workers aged 18-45 years from Zagazig University. The two groups filled out a questionnaire with 3 parts: sociodemographic and occupational data, the Premenstrual Symptoms Screening Tool (PSST), and the Work-Related Quality of Life Scale (WRQL). Results Severe PMS was reported in 45.8% of medical workers versus 20.8% of non-medical workers with a statistically significant difference between both groups (p = 0.009). Binary logistic regression showed that being a medical worker, clinical specialty, ≥ 8 years of work, ≥ 24 working hours per week, and having a non-set hourly schedule were predictors for severe PMS. PMS was found to be a statistically significant predictor of poor WRQL (p < 0.001). There was a highly significant negative correlation between the PMS score and the WRQL score (r =  − 0.302, p < 0.001). Conclusion Among medical workers, PMS is more common and more severe, and WRQL is worse and negatively correlated with PMS. We suggest further studies with larger samples to prove this association and planning for public health programs to screen for and manage PMS among medical workers in our community.